ASSESSMENT OF KNOWLEDGE, ATTITUDE AND PRACTICES (KAP) TOWARDS THE PREVALENCE OF WORK-RELATED MUSCULOSKELETAL DISORDER (WMSD) AMONG MALAYSIAN RAILWAY MAINTAINANCE WORKERS IN CONSTRUCTION SECTOR: A PILOT STUDY - Siti Maisarah Amdan; Siti Nurhafizah Saleeza Ramlee; Dian Darina Indah Daruis (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
One of the most commonly reported occupational diseases is Work-related Musculoskeletal Disorder (WMSD), which have shown a rising trend of exposure in the construction sector. Studies on worker’s Knowledge, Attitude, and Practices (KAP) on WMSD in the construction sector are limited. Hence, it is necessary to discover the underlying KAP factors in order to provide interventions to prevent MSDs. This study assesses the level of Knowledge, Attitude and Practice (KAP) on Work-related musculoskeletal disorder (WMSD) with the prevalence of WMSD among workers in construction sector. 30 workers from construction sector in Selangor were selected in this pilot study. All of them were specialised in railway maintenance work. There are two sets of questionnaires that were used throughout this pilot study: KAP on WMSD Questionnaire and CORNELL Musculoskeletal Questionnaire. Results showed the prevalence of WMSD is high at lower back body region (86.2%). Spearman correlation was used in order to test the relationship between KAP scores and KAP variables and prevalence of WMSD. The Kruskal Wallis test was used to test the KAP score and demographic. From Spearman correlation a significant relationship has been established between knowledge and practices (r= -0.483, p < 0.05) on KAP level of workers. Moreover, the attitude component has a significant difference (T= 8.411, p<0.05) with education level. The three highest prevalence of WMSD based on body region were found in lower back (86.2%), upper back (72.4%), and neck (65.5%). WMSD cases are increasing hence understanding the underlaying KAP factors in WMSD is crucial in order to deal with the problem. The findings will enhance awareness and engagement not only among employees but of all parties including industry players and stakeholders regarding WMSD and ergonomic hazards, leading to effective interventions and a safer working environment.